Effectiveness of a Cognitive Rehabilitation-Based Intervention on Cognitive Flexibility and Stereotyped Behaviors in Children with Autism Spectrum Disorder - Ramezani, Shahla (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: The present study aimed to examine the effectiveness of a cognitive rehabilitation-based intervention on cognitive flexibility and stereotyped behaviors in children with autism spectrum disorder. Methods and Materials: This study employed a quasi-experimental design with a pretest–posttest control group framework. The statistical population included all children aged 9 to 12 years with autism attending rehabilitation centers in Tehran in 2024. From this population, 30 participants were selected through convenience sampling and were randomly assigned to experimental and control groups. The research instruments included the Cambridge Neuropsychological Test Automated Battery (CANTAB) and the Gilliam Autism Rating Scale (GARS). The experimental group received cognitive rehabilitation intervention over eight sessions, while the control group received no intervention during the study period. Data were analyzed using analysis of variance (ANOVA) and the Kolmogorov-Smirnov test. Findings: The findings indicated that the cognitive rehabilitation intervention significantly increased cognitive flexibility (p < 0.01) and decreased stereotyped behaviors (p < 0.05) in the experimental group compared to the control group. Conclusion: These results support the effectiveness of cognitive rehabilitation in enhancing cognitive and behavioral functioning in children with autism spectrum disorder and suggest its potential use as a complementary method in therapeutic programs for these children.